PENGARUH BEBAN KERJA, STRES KERJA, KEPUASAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS NOMS KOPI SEMARANG) - Rosadi, Muhamad Alvin; Sijabat, Rauly; Darmaputra, M.Fajar (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
Several elements can shape an employee’s level of job satisfaction, including excessive workload, workplace stress, and inadequate compensation. When employees experience dissatisfaction in their roles, it often leads to a higher rate of turnover. This research investigates how workload, job-related stress, satisfaction levels, and compensation collectively influence employee performance. A saturated sampling approach was employed, meaning that every member of the target population participated as a respondent, totaling 70 individuals. The findings reveal that both workload and job satisfaction exert a positive influence on employee performance. In contrast, stress at work and compensation levels were found to negatively affect how well employees perform.